Financial costs of pediatric cancer management in Africa: systematic review - Mjumbe, Criss Koba; Kulimba, Desiré Mashinda; Numbi, Oscar Luboya; Nkumuyaya, Murielle; Balimo, Diane Muatama; Diyoka, Chadrack Kabeya; Ilunga, Benjamin Kabyla (Frontiers in Public Health, 2023)
The high costs of cancer treatment and the lack of investment in health care are significant barriers to public health on the African continent. The objective of this study was to investigate the financial cost of children cancer treating in sub-Saharan Africa. We systematically searched PubMed, Cochrane, and Google Scholar to identify relevant studies between March 2000 and December 2022. We selected articles that specifically addressed the US dollar financial costs of childhood cancer in African countries. Medians and interquartile ranges (IQR) were calculated. We also calculated the economic burden of childhood cancer at the individual level, by dividing the direct costs of cancer per patient by the GDP per capita, PPP of the country studied. The quality of economic studies was assessed using the CHEERS (2022) 28-point checklist. A total of 17 studies met our eligibility criteria. The median (IQR) of total childhood cancer costs by region was $909.5 ($455.3–$1,765) and ranged from $88803.10 for neuroblastoma to $163.80 for lymphoma. No significant differences (p < 0.05) were observed for comparisons of the direct cost of childhood cancer between the geopolitical zone of sub-Saharan Africa. Differences in the direct costs of childhood cancer were significant for different cancer types (p < 0.05). In the majority of 17 out of 54 countries on Africa the continent, the economic burden of childhood cancer exceeds 80% of GDP per capita, PPP, up to 345.38% of Nigeria’s GDP for Rhabdomyosarcoma. The cost of treating childhood cancers is high in Africa is catastrophic, if not downright prohibitive for households in Sub-Saharan Africa. We believe that the data from our study will be able to help make different objective advocacy allowing it to be provided with funds based of the evidence that can strengthen this program in order to install cancerology structures in the countries and by following the system plan. Cost reduction in the treatment of childhood cancer in particular and in general all types of cancer. Systematic review registration Approval of the study was given by the ethics committee of the Faculty of Medicine of the University of Lubumbashi (UNILU/CEM/135/2018) and (UNILU/CEM/096/2019).